Recovery of virus producing NDV vaccine by Tangential Flow Filtration (TFF) - Mel, Maizirwan; Arifin, Mohd Azmir; M Pauzi, Sazana (2009)
Currently, virus separation process is mainly conducted by using ultracentrifugation or sucrose gradient electrophoresis methods. Both methods however have several drawbacks wherein the ultracentrifugation method requires very high rotational speed to separate the virus while the sucrose gradient electrophoresis method is very time consuming. Alternative to both methods are by using Tangential Flow Filtration (TFF). In this study, we have separated and concentrated the Newcastle Disease Virus (NDV) harvested from embryonic specific pathogen free (SPF) eggs using TFF method by utilizing microfilter membrane with pore size of 0.45μm. Hollow fiber membrane was selected as filter because of their chemical and thermal stability. The study was conducted according to the design developed using Taguchi method which consists of selected three parameters and two levels of factors. The results revealed that higher pressure input (Pin), lower pressure output (Pout), and higher virus concentration led to higher virus titer. Optimum Trans-Membrane-Pressure (TMP) value of 15 psi and virus concentration of 28% had given the maximum titer of the virus which was 512 haemagglutination assay (HA) unit.